Recent Minority Situation in Croatia - Grbić, Jadranka (2000)
The presentation included various kinds of Croatian diaspora and minorities: old European diaspora, transcontinental diaspora, old and new minorities within Croatia, with special attention paid to developments in the 1990s.
Projekt MZOS
ENG